Evaluation of multidetector CT Hounsfield unit measurements as a predictor of efficacy and complications in percutaneous vertebroplasty for osteoporotic vertebral compression fractures - Yankov, Dimo; Bussarsky, Assen; Karakostov, Vasil; Sirakov, Alexander; Ferdinandov, Dilyan (Frontiers in Medicine, 2023)
Introduction: More than 30 years after the initial experience of Galibert and Deramond with percutaneous vertebroplasty, the procedure has gone through countless refinements and clinical evaluations. Predictors for the success and failure of the procedure in the literature vary and are focused on the duration of complaints, type of fracture, presence of edema on MRI scans, etc. We propose using a quantitative method based on a standard CT examination of the thoracic or lumbar spine to assess the risks and potential success of performing vertebroplasty.Material and Methods: This is a single-center prospective observational study on 139 patients treated with percutaneous vertebroplasty (pVPL) for a single symptomatic osteoporotic vertebral compression fracture (OVCF). We measured the levels of disability and pain preoperatively and again at the 3-, 6-and 12-month marks using the standardized VAS and ODI questionnaires. Every patient in the study was evaluated with postoperative multidetector CT (MDCT) to determine the presence, extent, and localization of vertebral cement leakage and to measure the adjacent vertebrae's minimal and mean density in Hounsfield units (HUmin and HUmean, respectively).Results: We determined that a slight (r=-0.201) but statistically significant (p=0.018) correlation existed between HU measurements taken from radiologically intact adjacent vertebrae and the procedure's effect concerning the pain levels at the 3-month follow-up. This correlation failed to reach statistical significance at 12 months (p=0.072). We found no statistically significant relationship between low vertebral cancellous bone density and cement leakage on postoperative scans (p=0.6 for HUmin and p=0.74 for HUmean).Conclusions: We have moderately strong data that show a negative correlation between the mean values of vertebral cancellous bone density in patients with OVCF and the effect of pVPL in reducing pain. Lower bone densities, measured this way, showed no increased risk of cement leakage.